Floating solar power loss due to motions induced by ocean waves: An experimental study - Huang, Luofeng; Yang, Yifeng; Khojasteh, Danial; Ou, Binjian; Luo, Zhenhua (Ocean engineering, 2024)
Whilst there is an interest in floating solar energy systems in coastal and offshore regions to utilise available sea space, they are subject to ocean waves that introduce constant momentum. Consequently, solar panels undergo periodic motions with the waves, causing a continuous change in tilt angle. The tilt angle variation is a sub-optimal process and leads to a loss of energy harnessing efficiency. To investigate this phenomenon, the present study innovatively installed a solar simulator on top of a wave tank. The solar simulator was used to generate high-strength light beams, under which, a floating solar unit was subject to periodic incident waves. Wave-induced motions to the solar system as well as the output power were measured. A systematic analysis of the results indicated that a floating solar unit can have significantly lower power output in waves, compared to its calm-water counterpart. An evident link was established between the wave-induced power loss and the wave-induced rotational movement of the panel. An empirical equation was derived which shows the power loss is predictable through the rotational amplitude. The results also highlight the importance of implementing wave attenuation technologies such as breakwaters to minimise wave-induced motions to floating solar systems. Overall, this research presents a novel experimental approach to assess the difference of floating solar power in ocean-wave versus calm-water scenarios, providing valuable insights for future solar projects on the ocean. •Floating solar panels with motions induced by ocean waves can lose energy due to varying tilt angle.•This work developed a new experimental facility, combining a solar simulator and a wave tank.•A floating solar system’s power output under the influence of wave-induced motions was tested.•To enable quick prediction of this power loss, an empirical equation is provided.•The application of breakwater with floating solar to minimise the wave-induced power loss is discussed.